Kolaborasi antara Peneliti dan Praktisi: Penelitian Interaktif pada Transformasi Digital di Credit Union Kridha Rahardja - Putra, Pande Putu Yuda Raditya Gunasta; Antonius Sumarwan; Titus Odong Kusumajati (Jurnal Bisnis dan Kewirausahaan, 2025)
Research findings of business management academics are often not applicable in solving concrete problems faced by business practitioners. This is due to the academic orientation that prioritize research with strict objectivity, while practitioners require research that address real-world issues. This syudy aims to bridge both interests by offering an interactive research approach. The research was conducted in collaboration with practitioners from Credit Union Kridha Rahardja, focusing on the case of digital transformation, specifically the achievements of the EsCeTe mobile banking application. The research succesfully increased the activation rates of EsCeTe, the frequency of EsCeTe transactions, and the transaction fees of EsCeTe, while also generating knowledge about actors and their capabilities in implementing digital transformation. Additionally, this study outlines the steps involved in condufting interactive research, along with the chalenges and solution to overcome them